2022
DOI: 10.9734/aprj/2022/v10i2187
|View full text |Cite
|
Sign up to set email alerts
|

Mirabilis jalapa Linn.: A Folklore Ayurvedic Medicinal Plant in Sri Lanka

Abstract: Mirabilis jalapa Linn. (Nyctaginaceae), commonly referred to as the Four O'clock plant (Sinhala name: Hendirikka), is a popular ornamental plant grown for the beauty of its flowers and used in folklore remedies. This plant is used to treat a variety of disease conditions around the world. It is widely used for abdominal colic, aphrodisiac, boils, diarrhea, inflammations, genitourinary disorders, muscular pain, and other issues by people from various countries. This plant contains several phytochemical compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Then allowed for cold macerating for about 1 week with frequent agitation (to preserve the heat labile phytochemicals). Then the micelle was filtered using a muslin cloth, obtained filtrate was concentrated using the rotary vacuum evaporator [19]. Extracts were collected into sterile air-tight containers and stored in the freezing compartment of the refrigerator until use [20].…”
Section: Preparation Of Aqueous Methanol Dichloromethane and Hexane E...mentioning
confidence: 99%
See 1 more Smart Citation
“…Then allowed for cold macerating for about 1 week with frequent agitation (to preserve the heat labile phytochemicals). Then the micelle was filtered using a muslin cloth, obtained filtrate was concentrated using the rotary vacuum evaporator [19]. Extracts were collected into sterile air-tight containers and stored in the freezing compartment of the refrigerator until use [20].…”
Section: Preparation Of Aqueous Methanol Dichloromethane and Hexane E...mentioning
confidence: 99%
“…Plants can be used to generate and isolate a large variety of phytochemical substances, as secondary metabolites. At the present time, several anti-inflammatory compounds originating from plants are being used as medicines and have no adverse side effects [12,13,14]. In Sri Lanka, medicinal plants have been used for centuries to treat a variety of inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Plants and their products have been used for centuries in complementary medicine to treat various human diseases [1][2][3][4]. According to studies, approximately 80% of the world's population relies on plant products for primary medical care [5][6][7][8][9]. These plant-based products possess multiple benefits over synthetic drugs, including being less expensive, more readily available, and having fewer side effects after either brief or prolonged consumption [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…There are about 1,414 medicinal plant species present in Sri Lanka. It is found that among them, around 250 species are commonly utilized while around 50 species are heavily involved [8][9][10]. The present example of Salacia reticulata Wight (HIPPOCRATEACEAE), also known as Kothala himbutu/ Himbutu wel by Sinhalese is a valuable species extensively utilized for its anti-diabetic properties [11].…”
Section: Introductionmentioning
confidence: 99%